Transforming Orality: The Podcast for Preserving Ecuadorian Traditions and Legends: Preservation of Cultural Heritage through Sound Narratives - Arrobo-Agila, Juan Pablo; Suing, Abel; Loyola Sarmiento, Mónica; Almachi Oñate, Ciro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study explores how the podcast format transforms Ecuadorian oral tradition into an effective tool for preserving intangible cultural heritage. Focusing on the provinces of Loja and Cotopaxi, ten stories were selected through simple random sampling, adapted into radio scripts and produced as podcast episodes. The process included the phases of pre-production, production, post-production and dissemination on platforms such as Spotify and Wix. The results highlight that the podcast recovers traditions, strengthens cultural identity and increases the audience. In addition, challenges such as the fragmentation of narratives and the integration of emerging technologies were identified.